A collaborative professional development and its impact on teachers' ability to foster higher order thinking - Cojorn, Kanyarat; Sonsupap, kanyarat (Journal of Education and Learning (EduLearn), 2024)
The objective of this research is to examine teachers' competence in designing activities after engaging in professional development activities aimed at enhancing teaching design in order to develop students' thinking abilities that are contextually appropriate. The participants consist of 5 elementary school science teachers from schools. The research employed semi-structured interviews and classroom observation as research instruments. The findings reveal that teachers engaged in self-development through observation and learning from their peers within the community of practice (CoP). They receive advice and feedback from fellow teachers and apply these insights to improve their activities. Consequently, teachers are able to continuously refine and develop their teaching approaches to align with students' contexts. This approach facilitate diversification in thinking and learning management, as well as collaborative teamwork to enhance teaching methods. As a result, engaging and interesting thinking development activities are incorporated into student learning, along with the creation of a seamless learning-promoting environment. Collaborative teamwork in instructional design and problem-solving further afford teachers the opportunity for additional self-learning and personal development. This collaborative approach also contributes to fostering cognitive diversity and relieved the need for individual teachers to undertake all tasks independently.